Kampung Bantang, Serian, Sarawak as a Tourism Area : Attractions and Challenges - Neilson Ilan, Mersat; Angelina, Ansley; Wong, Swee Kiong; Spencer Empading, Sanggin; Ahi, Sarok; Mohamad Suhaidi, Salleh; Mohd. Azizul Hafiz, Jamain (Universal Publishers - Boca Raton, Florida, 2018)
The objective of this paper is to discuss some of the major attractions identified in Kampung Bantang besides highlighting the challenges faced to make the village a tourism destination.